Construction of Gender in Linguistic Signs in Selected Kenyan Secondary School English Textbooks (Language Circle: Journal of Language and Literature, 2023)
In countries such as Kenya, where textbooks are a core component of classroom experience, the materials have the potential to shape socially enacted identities. Gender representation via linguistic signs in textbooks can have a substantial impact on how students perceive men and women in society. In order to achieve equity in education, which is a key mandate of both the Education for All (EFA) and Sustainable Development Goals (SDGs), gender bias in textbooks must be addressed. The National Policy on Gender and Development (NPGAD) in Kenya sought to enhance equal participation among men, women, girls and boys in education and other thematic areas. This paper contributes to the discourse on gender representation in textbooks by examining gender portrayal in linguistic signs found in selected English secondary school textbooks using Halliday’s (1985, 2014) systemic functional grammar approach. The study applied the explanatory sequential research design (Creswell Plano Clark, 2011). A document analysis guide derived from the model for analyzing linguistic signs by Halliday (1985, 2014) was employed in the analysis of quantitative data from the linguistic signs in four English textbooks. Results showed that in the selected textbooks, masculine representations were more prevalent than those of females. The study also revealed that males were more involved in all the three mood types namely; declarative, interrogative and imperative. Again, more males than females appeared as theme and rheme of clauses. Additionally, it emerged that males engaged more in verbal processes than females did. The study concludes that men are either implicitly or explicitly portrayed as being superior to women in the linguistic signs in the analysed textbooks. The study recommends that Ministry of Education in Kenya initiates measures to alleviate gender disparity by focusing on the issue of gender representation in textbooks. On the other hand, the Kenya Institute of Curriculum Development (KICD) may find these results useful in improving the textbooks evaluation based on gender equality prototypes. Improved evaluation, could be used as a basis to revise textbooks currently in use and guide in the development of new ones.